Oral mycophenolate mofetil prevents in-stent intimal hyperplasia without edge effect - Ilkay, Erdogan; Tirikli, Latif; Ozercan, Ibrahim; Yavuzkir, Mustafa; Karaca, Ilgin; Rahman, Ali; Arslan, Nadi (Sage Publications Inc, 2006)
Neointimal hyperplasia is in the forefront in in-stent restenosis. Prevention of in-stent restenosis is possible by reducing and inhibiting the hyperplasia of smooth muscle cells. The authors planned this study to test the hypothesis that when administered orally, mycophenolate mofetil (MMF) could inhibit in-stent neointimal hyperplasia. The study included 14 New Zealand rabbits. The rabbits were allocated to 2 different groups: Group I included 7 rabbits that were given MMF, 40 mg/kg/day by oral route. Group 2 included 7 rabbits that were not given MMF after the stenting. Sampling materials were taken before and after stenting by incising the artery so as to cover a 5-mm area. The samples taken from the edge of the stent in Group 1 showed focal neointimal cell proliferation, but it was less than that from the control group. Neointimal thickness was 0.048 +/- 0.009 mm and neointimal area was 0.0925 +/- 0.019 mm(2). Apparent neointimal cell proliferation and thickening of the intimal layer were observed in Group 2. Neointimal thickness at the stent edge was 0.147 +/- 0.051 mm and the neointimal area was 0.154 +/- 0.023 mm(2) The differences between groups in terms of neointimal thickness and neointimal area were statistically significant (p = 0.001 for thickness and p = 0.001 for area). In-stent artery samples of Group 1 showed that some subjects had no neointimal cell proliferation, while others had very limited focal intimal thickening. Neointimal thickening was 0.071 +/- 0.003 mm and neointimal area was 0.073 +/- 0.003 mm(2). In Group 2 apparent, and mostly focal, neointimal cell proliferation and formation of intimal layer were observed in the stent. Neointimal thickening was 0.154 +/- 0.069 mm and neointimal area was 0.279 +/- 0.059 mm(2). The comparison between groups showed significant differences (p = 0.011 for thickness and p = 0.001 for area). It was established in the third month that endothelialization was completed in both groups. Oral MMF decreased in-stent intimal hyperplasia without edge effect. It was concluded that for the prevention of in-stent restenosis, studies should be conducted for using systemic immuno suppressive treatments in humans as well.
Keywords: Coronary-Artery-Disease; Balloon-Expandable-Stent; Neointimal Proliferation; Intravascular Ultrasound; Eluting Stent; Coated Stents; Restenosis; Angioplasty; Implantation; Atherectomy